Effects of preoperative systemic administration of tranexamic acid alone on postoperative inflammation and pain in total hip arthroplasty: a retrospective cohort study - Fumihiro Mukasa; Tomonori Baba; Koju Hayashi; Taiji Watari; Muneaki Ishijima (Arthroplasty)
Abstract Background Recent studies have demonstrated that tranexamic acid (TXA) effectively reduces postoperative blood loss after total hip arthroplasty (THA) and is a safe treatment option. However, the anti-inflammatory effect of using TXA without dexamethasone (DEX) in THA remains unclear. In this study, we evaluated the anti-inflammatory effects, postoperative pain reduction, hidden blood loss (HBL), and postoperative complications associated with the use of TXA in THA. Methods This retrospective cohort study included 126 patients who underwent primary THA via a direct anterior approach (DAA) between January 1, 2023, and February 29, 2024. Patients were divided into two groups based on the administration of TXA (1000 mg IV preoperatively): Group A (with TXA) and Group B (without TXA). The postoperative inflammatory response (C-reactive protein [CRP] levels) and pain (numerical rating scale [NRS]) were assessed on postoperative days (PODs) 1, 3, and 7. HBL was assessed on PODs 3 and 7. Postoperative complications were counted based on occurrences from the postoperative period until discharge. Results CRP levels were significantly lower on POD 1 in Group A than in Group B (P = 0.002). Postoperative pain levels in Group A peaked later, with a significant reduction in the NRS score on POD 3, compared with that in Group B (P = 0.031). HBL in Group A was significantly reduced on PODs 3 (P < 0.001) and 7 (P = 0.013) compared to that in Group B. Postoperative complications did not differ significantly between Groups A and B. Conclusion TXA can effectively reduce postoperative blood loss, inflammation, and pain in patients undergoing THA without postoperative complications. Using TXA alone remains a highly effective and practical approach for improving early postoperative outcomes in patients undergoing THA.